Towards next generation design of sustainable, durable, multi-hazard resistant, resilient, and smart civil engineering structures. (15th February 2023) - Hao, Hong; Bi, Kaiming; Chen, Wensu; Pham, Thong M.; Li, Jun
Highlights: Discuss necessity, challenge and opportunity for next generation structures. Cover five key aspects for the construction of next generation structures. Critically review these five key aspects. Suggest research direction and design framework of next generation structures. Abstract: The design philosophy and methodology of civil engineering structures have been constantly evolving, from the early strength-based to more recent performance-based design and the current intensively researched emerging resilience-based design. Because failure of civil engineering structures often leads to catastrophic consequences, the primary focus of all these design methods is the safety of structures while considering other aspects such as performance and resilience. With the economic growth, population increase and urbanization, as well as global warming and the depletion of natural resources, to meet the societal need for sustainable development, the construction of civil engineering structures also needs to consider sustainability, durability and smart lifecycle management besides safety, performance and resilience. This paper discusses the necessity, challenge and opportunity for the development of the next generation design of sustainable, durable, multi-hazard resistant, resilient and smart civil engineering structures, which are named as SDuMuRS. Five key aspects are identified for the construction of next generation structures including: (1) sustainability; (2) durability; (3) multi-hazard resistance; (4) resilience; and (5) smart lifecycle structural health monitoring and management. Critical reviews and discussions on each of these aspects are presented. Research directions are suggested accordingly for achieving these goals for the design of next generation civil engineering structures. While this paper tries to cover as much as possible in the review and discussion of these five aspects, it by no means is inclusive of the relevant studies, but sheds light on these important aspects and opens the discussions for the development of next generation design of civil engineering structures.